FUNCTIONAL PERFORMANCE IN THE MODIFIED SHUTTLE TEST IN CHILDREN AND ADOLESCENTS WITH CYSTIC FIBROSIS - Luanna Rodrigues Leite; Karen Caroline Vasconcelos Queiroz; Cristiane Cenachi Coelho; Alberto Andrade Vergara; Márcio Vinícius Fagundes Donadio; Evanirso da Silva Aquino (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To evaluate factors associated with the performance of children and adolescents with cystic fibrosis (CF) in the Modified Shuttle Test (MST) and compare it with healthy children and adolescents. Methods: This is a cross-sectional study, with children and adolescents divided into two groups: cystic fibrosis (CFG) and control (CG). Variables evaluated in the MST: walking distance, test level, heart rate variation (∆Hr), post-test mean arterial pressure (MAP Pt) and peripheral oxygen saturation variation (∆SPO2). Statistical analysis included Mann Whitney and Spearman coefficient tests, being significant p<0.05. Results: Sixty individuals aged 6-16 years old were evaluated. Anthropometric data was similar between groups. Differences between groups were shown for: baseline heart rate (BHr), peak heart rate (PHr), ∆Hr, recovery heart rate (RHr), post-test respiratory rate (PtBr), saturation variables, peripheral oxygen level (SpO2B) and level test. The ∆Hr and MAP Pt had a moderate positive correlation with distance and level test for both groups (respectively: r=0.6 / p<0.001; r=0.6 / p<0.001). In CFG, the level test had a significant association (r=0.4 - p=0.02) with %FEV1. Conclusions: Children with cystic fibrosis presented functional limitation in the Modified Shuttle Test, which was influenced by lung function.